ELECTRONIC DOCUMENT FLOW IN THE PUBLIC ADMINISTRATION OF THE REPUBLIC OF BULGARIA: ESTABLISHMENT AND DEVELOPMENT - Lakhizha , M. (Theory and Practice of Public Administration, 2021)
The purpose of the study is to identify the status, specifics and problems of implementation and development of electronic document management in the public administration of the Republic of Bulgaria. It is noted that in recent years Bulgaria has become one of the countries with a high rate of e-government. However, it ranks last among the countries of the European Union. The process of transition to e-government was protracted, and administrations’ approaches to it were inaccurate and inefficient. The introduction of e-document circulation in Bulgaria took place in waves, which were prompted by political decisions recorded in regulations (2001, 2005, 2006-2008, 2014, 2017-2018). The informatization of Bulgaria took place under the significant influence of the European Union, which manifested itself not only in the need to adopt and comply with EU standards, but also financial, technological and educational assistance. The analysis confirms the complexity of the process of e-government development in the Republic of Bulgaria, its dependence not only on economic and technological opportunities, but also on the political, educational, psychological and other features of the country. Noting the significant amount of work carried out in Bulgaria on the legal support of e-government and e-document management, the author also notes that both state administrations and local governments had a low level of readiness to move to effective work with electronic documents.